2018
DOI: 10.1038/s41598-018-26975-4
|View full text |Cite
|
Sign up to set email alerts
|

HEV ORF3 downregulates TLR7 to inhibit the generation of type I interferon via impairment of multiple signaling pathways

Abstract: Hepatitis E is the most common type of acute hepatitis prevalent worldwide. The open reading frame 3 protein of HEV (HEV ORF3) is proposed to create a favorable environment for viral replication and pathogenesis. However, the mechanisms by which HEV overcomes the effects of host immunity, particularly the role of ORF3, remain to be established. Expression of IFNα and IFNβ in supernatant and cell samples was examined via ELISA and quantitative RT-PCR. The protein levels of specific signaling factors in cells ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Signal transducer and activator of transcription 3 (STAT3) expression can also be regulated, leading to a signi cant reduction of the in ammatory response. These ndings might provide strong support for the effect of ORF3 on virus replication [37][38][39][40]. Taken together, several functions of the ORF3 protein have already been reported.…”
Section: Discussionsupporting
confidence: 70%
“…Signal transducer and activator of transcription 3 (STAT3) expression can also be regulated, leading to a signi cant reduction of the in ammatory response. These ndings might provide strong support for the effect of ORF3 on virus replication [37][38][39][40]. Taken together, several functions of the ORF3 protein have already been reported.…”
Section: Discussionsupporting
confidence: 70%
“…The ORF3 of HEV1-Sar55 inhibits the production of type I IFNs in human monocytic THP1 and human hepatic Lo2 cells by inhibiting TLR3 and TLR7 expression [ 97 ]. Another group has reported that HEV1–Sar55 ORF3 inhibits the TLR3-mediated NF-κB activity in A549 cells [ 96 ].…”
Section: Virus Evasionmentioning
confidence: 99%
“…ORF3 as a multifunctional protein has been proposed to create a favorable environment for HEV infection and pathogenesis [99,100,101]. In respect to the regulatory effects on innate immunity, it has been shown to inhibit STAT1 phosphorylation and ISG expression upon HEV infection (Figure 1) [102].…”
Section: Viral Strategies To Counteract Innate Immune Responsementioning
confidence: 99%
“…ORF3 of genotype 1 has been reported to downregulate the expression of tumor necrosis factor receptor 1-associated death domain protein (TRADD) and receptor-interacting protein kinase 1 (RIP1), thus inhibiting TLR3 mediated activation of NF-κB upon poly (I:C) treatment [103]. In line with this, ORF3 inhibits the expression of endogenous IFNα/β through inhibiting the expression of TLR3 and TLR7 [99]. ORF3 also inhibits LPS-induced cytokines and chemotactic factors [56].…”
Section: Viral Strategies To Counteract Innate Immune Responsementioning
confidence: 99%
See 1 more Smart Citation